Awareness of Beneficiaries Regarding Public Distribution System/Food Security Bill. (2nd January 2017) - Diksha,; Kaushik, Sushma
ABSTRACT: The study was conducted to assess awareness and utilization of various provisions under Public Distribution System (PDS) and Food Security Bill (FSB) in Hisar district of Haryana state. Three urban and three rural Fair Price Shops were selected randomly and from each selected FPS, 25 beneficiaries were selected randomly, thus making a total sample of 150 beneficiaries. Data was collected personally by the researchers through a well-structured interview schedule. Findings revealed that majority of respondents had medium awareness regarding objectives, commodities available and mandatory display information while majority of respondents had low awareness regarding eligibility criteria of Public Distribution System (PDS)/Food Security Bill (FSB).